Of Mice and Men: In Vivo and In Vitro Studies of Primordial Germ Cell Specification - Kumar, Deepti Lava; DeFalco, Tony (Seminars in Reproductive Medicine, 2017)
Specification of mouse primordial germ cells (PGCs), the precursors of sperm and eggs, involves three major molecular events: repression of the somatic program, reacquisition of pluripotency, and reprogramming to a unique epigenetic ground state. Gene knockout studies in mouse models, along with global transcriptome analyses, have revealed the key signaling pathways and transcription factors essential for PGC specification. Knowledge obtained from these studies has been utilized extensively to develop robust in vitro PGC induction models not only in mice but also in humans. These models have, in turn, formed the basis for a detailed understanding of the signaling pathways and epigenetic dynamics during in vivo PGC specification and development. Recapitulation of human PGC specification in culture is of tremendous significance for understanding the mechanisms of human germ cell development in normal and disease states and has implications for addressing germ-cell–based causes of infertility.
Keywords: primordial germ cells; germ cell specification; pluripotent stem cells; epigenetic reprogramming